Rancang Bangun Smart Gloves Untuk Penyandang Disabilitas Sensorik Rungu Wicara - Fandhilah; Kasoni , Dian; ningsih, Liesna; Pardi, Muhammad (POLITEKNIK NEGERI JAKARTA, 2023)
Abstract - Communication is the most important need for humans as social beings to be able to interact with one human being and the other, for normal people communication does not experience obstacles. Unlike people with deaf and speech disabilities, they have difficulty communicating with others or with normal people, and normal people who do not understand sign language have difficulty interacting with the speech impaired and the deaf. For this reason, gloves are made as a communication aid for people with deaf and speech disabilities, these gloves can translate wetness of gestures by utilizing flex sensors on each finger segment. The data from the flex sensor is processed by Arduino Nano then the data is sent by the Bluetooth Transmitter and received by the Bluetooth Receiver then processed by Arduino Uno before being displayed on the 16x2 LCD, the final result after testing on the tool, the sensor is able to read letters and signal words, the accuracy rate of reading letter cues reaches 67% and word cues reach 44%, the sensor value always changes because the sensor reads the curve of the finger of the hand. ‘ Keywords: Communication, Sign Language, Gloves, Flex Sensors, Bluetooth.